PENERJEMAHAN IDIOM DALAM KOMIK HAYATE NO GOTOKU VOLUME 36 - Popy Lestari; Sri Wahyu Widiati; Zuli Laili Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The research discussed about the translation of idioms which contained in Hayate no Gotoku comic volume 36. The aim of this research is to know how the use of strategies and procedures in translation of idiom. The theories used in this research are translation strategies of idiom according to Baker (1992) and translation procedures according to Newmark (1988). The object of this research is Hayate no Gotoku comic volume 36 as the source language and translated comic into Indonesia language entitled Hayate the Combat Butler volume 36 as the target language. This research is a qualitative research which used descriptive method. The result of this research show that from 15 idioms, the strategies found that were, 1 idiom is translated by using an idiom of similiar meaning and form, 5 idioms are translated by using an idiom of similiar meaning but dissimiliar form, 8 idioms are translated by paraphrase, 1 idiom is translated by omission. Futhermore, the procedures found that were, 11 idioms are translated by free modulation procedure, 3 idioms are translated by standard modulation, and 1 idiom is translated by cultural equivalent procedure. Based on these results, the most commonly found translation strategies of idiom is translation by paraphrase and the most commonly found procedure is transpotition.Key Word : Idiom translation, Strategies, Procedures, Comic, Hayate the Combat Butler